EFFECTIVE SPEED TRACKING CONTROL OF PERMANENT MAGNET SYNCHRONOUS MOTOR USING DISTURBANCE OBSERVER AIDED SLIDING MODE CONTROL - Akhmetov, Miras (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This thesis presents the design and implementation of a robust speed tracking control strategy for Permanent Magnet Synchronous Motors (PMSMs) by integrating Sliding Mode Control (SMC) with a Disturbance Observer (DOB). PMSMs are widely used in industrial and high-performance applications because of their efficiency, compact size, and dynamic performance. However, they are vulnerable to external disturbances and nonlinear dynamics, which makes it harder to achieve a precise control To address these problems, an SMC is developed to ensure robustness against parametric uncertainties and external disturbances. The analysis includes both matched and mismatched disturbance cases. To improve the disturbance rejection, a DOB is added to estimate and compensate for external torques, frictional effects, and model inaccuracies in real-time. A comprehensive analysis of the system’s frequency-domain characteristics is conducted, showing how DOB parameters influence sensitivity and robustness. Simulation and experiments are carried out on a 300W PMSM. Comparative results between conventional PI control and the proposed SMC-DOB structure under different loads and inertia conditions reveal that the DOB-aided SMC provides superior tracking accuracy, faster transient response, and improved disturbance rejection. These results confirm the effectiveness of the proposed strategy for precise motion control in PMSM applications.
Keywords: type of access: open access; PMSM Speed Tracking; Sliding Mode Control; Disturbance Observer